Computational Neurology and Psychiatry - Érdi, Péter; Sen Bhattacharya, Basabdatta; Cochran, Amy L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents the latest research in computational methods for modeling and simulating brain disorders. In particular, it shows how mathematical models can be used to study the relationship between a given disorder and the specific brain structure associated with that disorder. It also describes the emerging field of computational psychiatry, including the study of pathological behavior due to impaired functional connectivity, pathophysiological activity, and/or aberrant decision-making. Further, it discusses the data analysis techniques that will be required to analyze the increasing amount of data being generated about the brain. Lastly, the book offers some tips on the application of computational models in the field of quantitative systems pharmacology. Mainly written for computational scientists eager to discover new application fields for their model, this book also benefits neurologists and psychiatrists wanting to learn about new methods.
From the Content -- Introduction -- Outgrowing Neurological Diseases: Microcircuits, Conduction Delay and Dynamic Diseases -- Extracellular Potassium and Focal Seizures - Insight From in Silico Study -- Time Series and Interactions: Data Processing in Epilepsy Research.
Keywords: Computational intelligence; Computer simulation; Neurosciences; Neural networks (Computer science) .; Computational Intelligence; Computer Modelling; Neuroscience; Mathematical Models of Cognitive Processes and Neural Networks